DIGITAL MARKETING AS AN IMPORTANT TOOL TO ENSURE THE BANK’S COMPETITIVE POSITION - Girchenko , Tetyana; Parhomenko , Karyna (Socio-economic relations in the digital society, 2021)
Abstract. The purpose of the article is to form scientific and methodological approaches to ensuring the competitiveness of banks based on the study of the role and importance of innovative technologies and digital marketing. The article analyzes the features of the development of the innovative component of ensuring the competitiveness of banks. Theoretical approaches to defining the essence of the concept of «digital marketing» and the main methods and tools it uses are studied. Methodical approaches to assessing the competitiveness of the bank in the implementation of digital marketing are considered. It is substantiated that the system of competitiveness assessment in the digital marketing system may consist of the following traditional (classic) and new (specific) media indicators: coverage — the share of the target audience, which was subject to the influence of the advertising message in a certain period of time; the latest indicators of interactive interaction: cursor hovering — cursor movement on an interactive object; click; transitions; user-generated content; registration in the CMS-system. The main goal and objectives for strengthening the competitiveness of the bank based on the introduction of digital marketing are identified, which include: renovation of branches in a new design and a new functional concept in accordance with modern customer needs; significant improvement of experience and increase of customer satisfaction from cooperation with the bank; introduction of changes in sales models and customer service with the use of modern electronic devices to ensure the active involvement of new customers; increase sales and promotion of the bank’s online products. The influence of digital marketing on the competitive position of the bank is analyzed, on the example of JSC «Raiffeisen Bank Aval» in terms of financial innovations. Keywords: competition; competitiveness; digital marketing; innovations; banking. JEL Classification M31, Z33, G21 Formulas: 0; fig.: 1; tabl.: 4; bibl.: 9.